Are hypothalamic- pituitary (HP) axis deficiencies after whole brain radiotherapy (WBRT) of relevance for adult cancer patients? - a systematic review of the literature - Mehta, P.; Fahlbusch, Fabian; Rades, D.; Schmid, S. M.; Gebauer, J.; Janssen, S. (BMC Cancer, 2019)
BACKGROUND: Cranial radiotherapy (cRT) can induce hormonal deficiencies as a consequence of significant doses to the hypothalamic-pituitary (HP) axis. In contrast to profound endocrinological follow-up data from survivors of childhood cancer treated with cRT, little knowledge exists for adult cancer patients. METHODS: A systematic search of the literature was conducted using the PubMed database and the Cochrane library offering the basis for our debate of the relevance of HP axis impairment after cRT in adult cancer patients. Against the background of potential relevance for patients receiving whole brain radiotherapy (WBRT), a particular focus was set on the temporal onset of hypopituitarism and the radiation dose to the HP axis. RESULTS: Twenty-eight original papers with a total of 1728 patients met the inclusion criteria. Radiation doses to the HP area ranged from 4 to 97 Gray (Gy). Hypopituitarism incidences ranged from 20 to 93% for adult patients with nasopharyngeal cancer or non-pituitary brain tumors. No study focused particularly on hypopituitarism after WBRT. The onset of hypopituitarism occurred as early as within the first year following cRT (range: 3 months to 25.6 years). However, since most studies started follow-up evaluation only several years after cRT, early onset of hypopituitarism might have gone unnoticed. CONCLUSION: Hypopituitarism occurs frequently after cRT in adult cancer patients. Despite the general conception that it develops only after several years, onset of endocrine sequelae can occur within the first year after cRT without a clear threshold. This finding is worth debating particularly in respect of treatment options for patients with brain metastases and favorable survival prognoses.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Endocrine deficiencies; Hypopituitarism; Hypothalamus; Pituitary; Whole brain radiotherapy